2020
DOI: 10.1186/s12889-020-09971-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice regarding antibiotic use and resistance among medical students in Colombia: a cross-sectional descriptive study

Abstract: Background This study was designed to describe the knowledge, attitude, and practice regarding antibiotic use and resistance among medical students in Medellín, Colombia. Methods A cross-sectional study was conducted among medical students from three universities from September to December 2018. The sample size was calculated, the classrooms were visited, and those students who were willing to participate were invited to do so. The data collection instrument was constructed in three stages: i) the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
(42 reference statements)
4
31
1
Order By: Relevance
“…However, a study conducted in Malaysia reported a much lower percentage (48.5%) for perceived impact of antibiotic resistance on the participants and their family. Contrary to findings reported by previous studies [ 2 , 20 , 51 , 52 ], an intriguing research finding in this study was that only 52% of the participants recognized antibiotic resistance as one of the greatest challenges the world faces today. The main reason could be attributed to lack of knowledge as only 46.8% of the participants believed that antibiotic resistance is an issue that is not limited to Jordan but also concerns other countries.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a study conducted in Malaysia reported a much lower percentage (48.5%) for perceived impact of antibiotic resistance on the participants and their family. Contrary to findings reported by previous studies [ 2 , 20 , 51 , 52 ], an intriguing research finding in this study was that only 52% of the participants recognized antibiotic resistance as one of the greatest challenges the world faces today. The main reason could be attributed to lack of knowledge as only 46.8% of the participants believed that antibiotic resistance is an issue that is not limited to Jordan but also concerns other countries.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the perceptions and knowledge scores of the respondents suggested that there were deficiencies in the US medical school curricula, including fundamental concepts of antimicrobial usage. Interestingly, similar studies conducted in different countries such as China, Colombia, Singapore and Italy have shown similar results [ 33 ]. A formal evaluation of the curricula of medical schools regarding education about antimicrobials needs to be evaluated, and the introduction of concepts of the molecular aspects of bacterial resistance in general microbiology courses is strongly recommended.…”
Section: Activities For Medical Studentssupporting
confidence: 54%
“…The lowest possible score was 13, and the highest possible score was 65 for the practice section. The scores then were transformed to a scale ranging from 0 (worst possible score) to 100 (best possible score) with the formula (Equation ( 1)) [54,56]. The total score of <50%, 50-70%, and >70% were categorized as low, moderate, and high knowledge, attitude, and practice, respectively [28].…”
Section: Data Instrument and Collectionmentioning
confidence: 99%